A CMAQ-based Study on Evaluation of Achievements of Measures on Ozone Pollution Prevention and Control in Summer 2017 in Chengdu. Issue 1 (November 2020) - Liu, Hefan; Deng, Ye; Lu, Chengwei; Zhang, Xin; Yang, Xinyue; Song, Danlin; Tan, Qinwen
Abstract: Ozone Pollution is one of the major difficulties in improving the air quality of Chengdu. In 2017, on the basis of research findings including a mass of observation data, meteorological data and numerical simulation data of air quality on the localized ozone and its precursors in Chengdu, Chengdu Environmental Protection Bureau drew up and implemented 2017 Chengdu Ozone Pollution Prevention and Control Action Program (OPCAP). This study elaborated on the specific measures of OPCAP and the subject of implementation of the said measures, and based on the localization of CMAQ parameters, conducted scientific evaluation on the achievement of OPCAP implementation. The research findings are set forth as follows: OPCAP made pollutants reduced to a large extent, for example, the industrial emissions of VOCs and NOx were reduced by 8600 tons and 2150 tons, respectively. Compared to the corresponding period of last year, in August 2017, meteorological change made O3max, PM10, PM2.5, NO2 and CO reduced by 34.9%, 24.2%, 23.9%, 16.6% and 6.0%, respectively. After a series of measures including OPCAP were taken, O3_8h max was reduced by 6∼10μg/m 3 in most areas of Chengdu. Under equal meteorological conditions in August 2017, OPCAP made O3_8h max in the downtown of Chengdu reduced by 3.67% on average, and the concentration of NO2, SO2, PM10, PM2.5 and CO was reduced by 25.00%, 11.11%, 19.59%, 19.63% and 5.32% on a monthly average basis. As shown above, it can be seen that OPCAP worked on ozone pollution prevention and treatment. The technologies adopted in and the findings of this study may provide technological guidance on the mid-term and long-term ozone pollution prevention and treatment.